2011 IEEE Vehicle Power and Propulsion Conference 2011
DOI: 10.1109/vppc.2011.6043185
|View full text |Cite
|
Sign up to set email alerts
|

Predictive gear shift control for a parallel Hybrid Electric Vehicle

Abstract: In this paper, Model Predictive Control (MPC) framework is exploited to synthesize a predictive controller for a parallel Hybrid Electric Vehicle (HEV) equipped with an Automated Manual Transmission. The algorithm also controls the gear shift command, together with the power split between the engine and electric machine and the engine on-off state using the route information ahead. A non-predictive controller based on a combination of Dynamic Programming (DP) and Pontryagin's Minimum Principle (PMP) is describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Configuration with single motor and two-speed transmissions (SMTST) [8,9] offers potential for system efficiency improvement owing to the controllable gear ratio. Studies on gear train design, gear shift control, and ratio optimization have been carried out [10][11][12]. Results have confirmed the benefits of the SMTST scheme on economy improvement.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Configuration with single motor and two-speed transmissions (SMTST) [8,9] offers potential for system efficiency improvement owing to the controllable gear ratio. Studies on gear train design, gear shift control, and ratio optimization have been carried out [10][11][12]. Results have confirmed the benefits of the SMTST scheme on economy improvement.…”
Section: Introductionmentioning
confidence: 70%
“…2 ) and out response ( dis ) is a high-degree polynomial, taking sixth-degree polynomial as example as shown in formula (11). Currently, least squares method is most commonly used to obtain the formula coefficients but may have singular matrix problem.…”
Section: Mathematical Model For Energymentioning
confidence: 99%
“…However, few references propose systematic methods to design shift schedule for HEVs. Existing solutions found in the literature are based on heuristic techniques and engineering experiences, such as using the throttle opening and vehicle speed as reference parameters [18][19][20][21]. Due to the high coupling of the power sources in the power-split HEVs, the characteristics and efficiency of the MGs and battery will result in different results from those of conventional vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Baraszu and Cikanek demonstrated that during the gearshifting process a motor should provide torque directly to reduce the power interruption time [7]. A combination of Dynamic Programming (DP) and Pontryagin's Minimum Principle (PMP) was utilized in a model predictive controller framework to realize a predictive controller in a receding horizon mode for a PHEV equipped with an AMT [8]. The computational burden and assumption that velocity profile is available ahead limit its application in real-time control.…”
Section: Introductionmentioning
confidence: 99%